Advances in Neuroimaging Techniques for the Diagnosis of Headaches (Journal SCIENCEVOLUTION, 2025)
Headaches are among the most common and disabling neurological disorders worldwide, posing ongoing challenges for differential diagnosis. Therefore, this review aimed to analyze the significant advances in neuroimaging techniques and their impact on headache diagnosis. A narrative literature review was conducted, drawing on 42 scientific articles published between 2015 and 2025 in indexed databases such as PubMed, Scopus, and ScienceDirect. The hermeneutic method was applied to examine structural and functional techniques. The findings indicate that multimodal integration and artificial intelligence have enhanced diagnostic accuracy by enabling the identification of biomarkers, the differentiation of complex etiologies, and a deeper understanding of the pathophysiological mechanisms of pain, surpassing the limitations of conventional imaging. However, constraints related to protocol standardization and access to advanced technologies were identified. It is concluded that advanced neuroimaging techniques are essential tools for differential diagnosis and for the transition toward personalized medicine, provided their use is guided by clinical red flags and rigorous ethical considerations.
Keywords: Neuroimaging; Migraine; Headache Disorders; Functional Magnetic Resonance Imaging (fMRI); Diffusion Tensor Imaging (DTI); Positron emission tomography (PET); Multimodal Imaging; Artificial Intelligence; Biomarkers; Glymphatic System